مبدأ السيادة الرقمية الفردية على البيانات - عبدالغفار، أحمد محمد محمد (جامعة الأزهر - كلية الشريعة والقانون بدمنهور, 2023)
أدت بعض الانحرافات المدفوعة بالمصالح الاقتصادية، والتجارية لوسائل التواصل الاجتماعي إلى بلورة تحديات جديدة على مستوى حماية البيانات الشخصية، وبالأخص مع تغلغل تكنولوجيا إنترنت الأشياء، والحوسبة السحابية، والذكاء الاصطناعي ...؛ حيث زاد نطاق جمع، وتبادل، ومعالجة البيانات بشكل غير مسبوق؛ مما سمح للشركات، والأفراد، باستغلال المعلومات الشخصية للأفراد على نطاق واسع؛ وهو ما يحول- بدوره دون التخلص من الماضي البغيض أو حتى المسبب للإحراج؛ لتشكل بذلك تهديدا لأركان الكيان الإنساني في محيطه العائلي، والاجتماعي، ....، ولعل تلك المعطيات كانت بمثابة الدافع إلى تكريس فكرة السيادة الفردية على البيانات من منظور الحق في الاستقلال المعلوماتي؛ لينتقل الحق في حماية البيانات، والسيطرة الإرادية عليها من مجرد الحق الدفاعي إلى مرحلة الطابع الإيجابي الهجومي؛ من خلال تعزيز موافقة الأفراد على معالجة بياناتهم، والتأكيد على الحقوق الناشئة للأفراد في ظل طفرات الثورة الرقمية. والحق الاستقلال المعلوماتي- وفقا لهذا المبدأ- ينشئ مفهوما جديدا للعلاقة بين الشخص، (المعني بالبيانات)، وبياناته، يمنح كل فرد استقلالية معينة في إدارة بياناته الشخصية؛ من خلال تعزيز موافقة الأفراد، والتأكيد على الحقوق الرقمية الجديدة للأشخاص المعنيين ضمن الفضاء الإلكتروني. ومع الأهمية البالغة للحق في الاستقلال المعلوماتي إلا أنه قد تعرض للعديد من الانتقادات التي ما لبثت أن انهارت أمام طغيان الثورة الرقمية، بل وبات حق الاستقلال المعلوماتي يشكل حجر الزاوية في النظام القانوني؛ لحماية المجال الخاص في العصر الرقمي، ويضمن للجميع الحق في اتخاذ قرار بشأن الإفصاح أو الكشف أو الاستخدام لبياناتهم؛ لذلك ارتقى هذا الاجتهاد الفقهي إلى مرتبة الحقوق الدستورية ليستقر – مؤخرا- ضمن تلك الحقوق الأساسية للأفراد في غالبية أنظمة القانون المقارن. Some deviations driven by the economic and commercial interests of social media have led to the crystallization of new challenges at the level of personal data protection, especially with the penetration of Internet of Things technology, cloud computing, and artificial intelligence...; Where the scope of collecting, exchanging, and processing data has increased in an unprecedented way; This allowed companies and individuals to exploit personal information on a large scale; Which, in turn, prevents getting rid of the unpleasant or even embarrassing past. To thus constitute a threat to the pillars of the human entity in its familial and social surroundings..., Perhaps these data served as a motive for devoting the idea of individual sovereignty over data from the perspective of the right to informational independence; Thus, the right to data protection and voluntary control over it moves from a mere defensive right to the stage of an offensive positive nature. By enhancing individuals' consent to the processing of their data, and emphasizing the emerging rights of individuals in light of the booms of the digital revolution. The right to informational independence- according to this principle - establishes a new concept of the relationship between the person (concerned with the data) and his data, granting each individual a certain independence in managing his personal data. By promoting individual consent, and asserting the new digital rights of interested persons in cyberspace. Despite the extreme importance of the right to informational independence, it was subjected to many criticisms that soon collapsed in the face of the tyranny of the digital revolution. Indeed, the right to informational independence has become a cornerstone of the legal system To protect the private sphere in the digital age, and guarantee everyone the right to decide on the disclosure, disclosure or use of their data; Therefore, this jurisprudence has risen to the rank of constitutional rights to settle- recently- within those basic rights of individuals in most comparative law systems.
Keywords: البيانات الرقمية -- الأنظمة القانونية -- الفضاء الإلكتروني -- التحول الرقمي -- المعاملات الإلكترونية